The Emotional Filter: Investigating Attitude towards Emotions as a Moderator in the Self-Efficacy-Happiness Connection - Bhalla, Pretty; Kaur, Jaskiran; Alharbi, Ameen; Qazi, Sayeeduzzafar (Journal of Posthumanism, 2025)
This primary and exploratory study investigates the intricate dynamics of the self-efficacy-happiness connection, with a specific focus on the moderating role of attitudes towards emotions. A structured questionnaire was employed to gather responses from 358 working professionals, utilizing a combination of in-person distribution and electronic dissemination through Google Forms. Through meticulous coding and analysis, the study delves into two primary objectives. First, it scrutinizes the impact of self-efficacy on happiness. Second, it explores the moderating influence of attitudes towards emotions on the relationship between self-efficacy and happiness. Employing quantitative tools such as mediation analysis with SPSS 23.0 and AMOS 22.0, the research aims to uncover nuanced insights that can inform targeted interventions for promoting emotional well-being and happiness among diverse populations of working professionals. The robust methodology ensures a comprehensive examination of the variables, paving the way for practical applications in areas such as mental health interventions, educational strategies, and workplace initiatives.